ANALYSIS OF THE UTILIZATION OF POSYANDU JIWA IN THE BLOTO PUBLIC HEALTH CENTER AREA IN 2025 - Imam Zainuri; Lilik Ma’rifatul Azizah; Amar Akbar; Siti Khotijah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Mental health is part of the health status that must be achieved at the optimal level. Indicators that can be used include a decrease in psychosocial problems and the incidence of people with mental disorders (ODGJ). A service that plays a fundamental role and directly impacts the community is Posyandu Jiwa. This service is provided by the community, from the community, and for the community. The main service providers at Posyandu are mental health cadres under the guidance and support of health workers at the local Community Health Center. Posyandu Jiwa provides services for people with mental disorders (ODGJ). Services provided include regular health screenings, skills or vocational development, spiritual guidance, Group Activity Therapy (TAK), and family therapy. The purpose of this study was to analyze the utilization of Posyandu Jiwa in the working area of Bloto Health Center in 2025. This type of research is quantitative with a Cross Sectional approach. The sampling technique is total sampling. The research data were obtained from questionnaires on ODGJ knowledge, cadre behavior, family support, and ODGJ motivation. Data analysis using Chi square. There is a relationship between knowledge and the utilization of Posyandu Jiwa in Bloto Health Center in 2025 with a p-value = 0.000 (p <0.05). There is a relationship between cadre behavior and the utilization of Posyandu Jiwa in Bloto Health Center in 2025 with a p-value = 0.001 (p <0.05). There is a relationship between family support and the utilization of Posyandu Jiwa in Bloto Health Center in 2025 with a p-value = 0.001 (p <0.05). There was a correlation between patient motivation and utilization of the Posyandu Jiwa (Mental Health Post) at the Bloto Community Health Center in 2025, with a p-value of 0.002 (p < 0.05). The factor most closely related to Posyandu Jiwa utilization was knowledge, with a p-value of 0.001 (p < 0.05). One effort that needs to be improved to further optimize Posyandu Jiwa utilization is to improve knowledge among cadres, families, and cooperative individuals with mental disorders.